Evaluation of terminal blend rubberized asphalt incorporating high crumb rubber content - Yangquan Huang; Kun Long; Chi Qu; Chuanqi Yan; Changfa Ai; Shengxiong Zhou (Case Studies in Construction Materials)
Currently there has been a trend of increasing the rubber content in rubberized asphalt due to the obvious environmental and decarbonizing benefits of this technology. Terminal Blend Rubberized Asphalt (TBRA) appears to be a feasible approach to safely increase the waste rubber content within the asphalt binder. This study attempts to discuss the feasibility of highly-dosed TBRA and conduct a comprehensive evaluation on this modified asphalt. To do so, TBRA of different rubber contents (30%, 40%, 50%) are produced. To achieve high desulfurization and thermal degradation of the CR particles, enhancing the stability and processability of the TBRA samples, higher preparation temperatures (220°C) and extended shearing times (6 hours) were employed. The study assesses how these production conditions affect the asphalt's microstructure, chemical composition, and viscoelastic properties, using fluorescence microscopy, ATR-FTIR, and rheology master curves for analysis. Results show that the terminal blending process leads to CR particle breakdown and rubber molecule depolymerization, enhancing workability and stability up to a rubber dosage limit of approximately 40 %. However, while TBRA shows excellent low-temperature performance and fatigue resistance, its high-temperature properties are moderate, suggesting further modifications with materials like SBS or rock asphalt could enhance its performance.